Theory of Emergence and the Problem of Downward Causation - Bratina, Sibin B. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The author examines the theory of emergence and the consequences of accepting such a framework. This theory conceives of the world as structured in layers, where each layer is defined by wholes that are more than the sum of their parts. Since discussions about emergence are usually situated in relation to physicalism, this paper follows the ontological implications of the theory for materialist metaphysics. Specifically, it raises the question of the ontological status of new properties that arise at levels above the physical layer of a given structure. One attempt to account for this relationship is the notion of supervenience. Ultimately, these ideas lead to the problem of downward causation, which is analyzed at the end of the paper in an effort to find a theoretical space for its resolution.
Keywords: emergence; physicalism; causation; ontology; structure